Reparación y reconciliación en el sistema normativo Wayuu. (2016)
This article explains what constitutes reparation and reconciliation in the wayuu normative system. The purpose is to make visible a practice of justice application that seeks to restore harmony between the clans of this ethnic group (located in the peninsula of Guajira, Colombia), when it is broken by aggression from one to another. To achieve this goal the conception of impunity for the wayuu is shown. As well as the effects of reparation in society, and how reconciliation is achieved. In general, the article tries to demonstrate the hypothesis of the investigation of how the system of norms is sustained in the culture of this people.